Humanism, reform, and the Reformation: the career of Bishop John Fisher - Bradshaw, Brendan; Duffy, Eamon (Cambridge University Press, 1989)
This book assembles ten special studies, each devoted to an aspect of Fisher's multifaceted career or to exploring the intellectual and religious outlook of someone who was at the same time a moderniser, a reformer and an opponent of the Reformation. John Fisher's career provides an illuminating perspective on English religious and intellectual history in a crucial phase of development. As a churchman he became the foremost preacher in England, issuing a call to ecclesiastical reform and personal repentance that echoed the call of Savonarola at Florence. At the same time he provides an early example of the pastoral bishop that was to become the ideal of both the Reformation and the Counter Reformation. Finally in the crisis that paved the way for the English Reformation, he became the leading defender of Queen Catherine against the divorce suit of Henry VIII. He was among the small band who were executed in 1535 as conscientious objectors to the oaths of Succession and Royal Ecclesiastical Supremacy. He has been venerated as a Catholic martyr ever since.